2021
DOI: 10.1088/1361-6463/abe89a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning plasma parameters to control reactive species fluxes to substrates in the context of plasma catalysis

Abstract: The key reactive plasma-produced gas phase species responsible for the enhanced conversion of chemicals in plasma catalysis compared to thermal catalysis have to date not been identified. This outstanding question is mainly due to the inherent large variety of plasma-produced species and the challenge of controlling and measuring the flux of each constituent of the cocktail of reactive species to a (catalytic) substrate. In this paper, we explore the possibility to control the dominant reactive species fluxes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…However, the other two ROSs, singlet oxygen and ozone, do not show any obvious correlation. The flux of the consumed CH 4 , produced CO and CO 2 is proportional to the atomic O flux delivery to the catalytic bed, and the curves coincide for all O 2 flow rates at a catalyst temperature of 25 • C. As the ion flux and UV flux are very small for these jet conditions [50,54], these observations are consistent with the hypothesis that atomic O is the key reactive species that contributes to the reaction. Luan et al [55] studied polymer etching using a similar APPJ, and they found that the etching depth of the polymers mirrors the flux of atomic O produced from the APPJ, and a similar proportional relationship between the etching depth and atomic O flux was established.…”
Section: Correlation Between Ch 4 Conversion and Atomic O Fluxsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the other two ROSs, singlet oxygen and ozone, do not show any obvious correlation. The flux of the consumed CH 4 , produced CO and CO 2 is proportional to the atomic O flux delivery to the catalytic bed, and the curves coincide for all O 2 flow rates at a catalyst temperature of 25 • C. As the ion flux and UV flux are very small for these jet conditions [50,54], these observations are consistent with the hypothesis that atomic O is the key reactive species that contributes to the reaction. Luan et al [55] studied polymer etching using a similar APPJ, and they found that the etching depth of the polymers mirrors the flux of atomic O produced from the APPJ, and a similar proportional relationship between the etching depth and atomic O flux was established.…”
Section: Correlation Between Ch 4 Conversion and Atomic O Fluxsupporting
confidence: 78%
“…Figure 8(a) shows that increasing the O 2 admixture to Ar/O 2 feed gas decreases the consumption of CH 4 at 25 • C. The addition of O 2 to the plasma source leads to the quenching of high-energy electrons, metastable species and reactive oxygen species [37,[50][51][52], resulting in the decrease of plasmainduced reactivity. The plasma plume length also decreases significantly upon increasing O 2 addition [52].…”
Section: Effects Of O 2 Additives On Decomposing Chmentioning
confidence: 99%
“…A radiofrequency-driven atmospheric pressure plasma jet (ID = 2 mm, OD = 3 mm) was coupled with a packed bed of metal wools downstream of the plasma in this study. The plasma jet was similar to the one described by Jiang and Bruggeman, with the ground electrode lengthened to 3 cm. The setup of the plasma jet is described in more detail by Kondeti et al with the method for power measurement described by Hofmann et al The plasma jet was driven at 12.8 MHz with two duty cycle modulations, 20 kHz at 50% and 50 Hz at 50% (Supporting Information, S.2).…”
Section: Methodsmentioning
confidence: 76%
“…The synergy reflects the complex interdependence of plasmas and catalysts: the plasma affects the catalyst properties and vice versa-the catalyst affects the plasma properties. As reviewed by Neyts et al [29], on one hand, the effects of plasmas on catalysts include the variation in physical and chemical properties of the catalysts [30][31][32], the formation of hot spots [33], photon irradiation [34][35][36][37], reduction of the activation barrier [38,39], and change in the reaction pathways [40][41][42]. On the other hand, effects of catalysts on plasmas involve the electric field enhancement [43], the formation of microdischarges in holes [44,45], the variation of the discharge form [43,46], and adsorption of plasma species on the catalyst surface [47,48].…”
Section: Introductionmentioning
confidence: 99%